2012
DOI: 10.1037/a0024160
|View full text |Cite
|
Sign up to set email alerts
|

Gene-environment interplay in the association between pubertal timing and delinquency in adolescent girls.

Abstract: Early pubertal timing places girls at elevated risk for a breadth of negative outcomes, including involvement in delinquent behavior. While previous developmental research has emphasized the unique social challenges faced by early maturing girls, this relation is complicated by genetic influences for both delinquent behavior and pubertal timing, which are seldom controlled for in existing research. The current study uses genetically informed data on 924 female-female twin and sibling pairs drawn from the Natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(49 citation statements)
references
References 135 publications
3
46
0
Order By: Relevance
“…Notably, we do not find a direct link between early puberty and externalizing, in keeping with some previous studies (Negriff & Trickett, 2010) but not others (Caspi et al, 1993). Reasons for this may include the way externalizing was measured, given that previous research suggests that early puberty predicted only non-violent forms of delinquency (Harden & Mendle, 2012); and that research with clinical samples such as ours (Negriff & Trickett, 2010) and racially diverse samples such as ours (Deardorff et al, 2013; Obeidallah, Brennan, Brooks-Gunn, & Earls, 2004) with similarly aged girls does not find a direct effect of early puberty on externalizing symptoms. Finally, we did not find evidence that the presence of older boyfriends alone predicts either internalizing or externalizing symptoms, corroborating previous studies (Javdani et al, 2014) suggesting that the influence of older boyfriends does not persist past early adolescence (Haydon & Halpern, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, we do not find a direct link between early puberty and externalizing, in keeping with some previous studies (Negriff & Trickett, 2010) but not others (Caspi et al, 1993). Reasons for this may include the way externalizing was measured, given that previous research suggests that early puberty predicted only non-violent forms of delinquency (Harden & Mendle, 2012); and that research with clinical samples such as ours (Negriff & Trickett, 2010) and racially diverse samples such as ours (Deardorff et al, 2013; Obeidallah, Brennan, Brooks-Gunn, & Earls, 2004) with similarly aged girls does not find a direct effect of early puberty on externalizing symptoms. Finally, we did not find evidence that the presence of older boyfriends alone predicts either internalizing or externalizing symptoms, corroborating previous studies (Javdani et al, 2014) suggesting that the influence of older boyfriends does not persist past early adolescence (Haydon & Halpern, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, this study identified pathways of risk for early-maturing maltreated youth. There is evidence that the same genes that influence the timing of puberty also predict risk behavior and that environmental experience may modify the expression of these genes[39]. Particular attention should be paid to this vulnerable population with efforts to increase the positive socialization of these youth.…”
Section: Discussionmentioning
confidence: 99%
“…Other changes in sex hormones also differentially influence girls. Increased levels of estrogen have been shown to augment the reactivity of the reward system in women (Dreher et al, 2007), and menarche has been associated with earlier initiation and greater frequency of a range of unhealthy behaviors including substance use (Westling et al, 2008) and delinquent behavior (Harden and Mendle, 2012). Although evidence is mixed, some research suggests that sex steroids (estradiol, testosterone) may be differentially associated with risk behavior and social processing in adolescent girls and boys (e.g., CastellanosRyan et al, 2013).…”
Section: Focus On Girlsmentioning
confidence: 99%